Implikasi Putusan MK No 62 Tahun 2024 Terkait Penghapusan Presidential Threshold - Nur Alfi Rahmayanti; Ikhsan Fatah Yasin (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
There has been an elimination related to the presidential threshold in proposing presidential and vice presidential candidates by political parties in the Constitutional Court Decision Number 62/PUU-XII/2024 which tests Law Number 7 of 2017 concerning General Elections against the 1945 Constitution of the Republic of Indonesia. Regarding the elimination of the presidential threshold, it will bring significant changes to the general election system in Indonesia. This study aims to analyze the implications of the decision from a legal perspective and political reality through a juridical-normative approach and political analysis, this study finds that the elimination of the presidential threshold has the potential to expand the political participation of new and small parties, as well as independent candidates, but on the other hand it can also pose a risk of political fragmentation and government instability. The results of this study are expected to contribute to understanding the long-term impact of the Constitutional Court's decision on democracy and governance in Indonesia.